Astronauts : women on the final frontier - Ottaviani, Jim (First Second, 2020)
Presents a graphic novel history of women in space, exploring the struggles that both American and Russian women, including Mary Cleave, Valentina Tereshkova, and Sally Ride, faced in their quest to become astronauts.